Aquatic macroinvertebrate trophic guilds, functional feeding groups, and water quality of an andean urban river - Carrasco-Badajoz, Carlos; Rayme-Chalco, Carolina; Arana-Maestre, Jerry; Álvarez-Tolentino, Daniel; Ayala-Sulca, Yuri; Sanchez-Peña, Marco (Frontiers in Environmental Science, 2022)
In the Anthropocene, man has imposed his activities above the natural processes of ecosystems. Rivers have undergone major changes associated with urban centers, so monitoring them is important to determine their status and suitability to provide environmental services. Studies applying the community ecology approach, such as energy flow in aquatic macroinvertebrate assemblages, may be appropriate to determine their status and functioning. This study characterized an Andean river that runs across the city of Ayacucho (Peru). We used water physicochemical parameters and biotic quality indices and compared them with the abundance of trophic guild components and functional feeding groups to demonstrate that the latter are at least equally suitable to estimate water quality. The river section studied ranged from 2640 to 2900 m a.s.l. and was monitored in the wet and dry seasons. Six monitoring stations were established according to the extent of the influence of the urban center. Physicochemical variables of water and macroinvertebrates were determined. A Surber net was used for multihabitat sampling; macroinvertebrates were identified to genus (in most cases) and counted to estimate relative abundances. Trophic guilds (detritivore, predator, herbivore) were formed using the identification to genus according to the information available in Argentina, Colombia, Ecuador, Bolivia, and Peru, and functional feeding groups were set based on the classification of families. The sensitivity of trophic metrics was assessed by relating them to environmental variables and the ABI, BMWP/Col., and EPT indices. Environmental variables and biotic indices increase significantly in the most impacted stations, where the abundance of most taxa decreases. The components of trophic guilds and functional groups vary, and those feeding on fine particles increased in sites with a higher urban impact. The metrics based on trophic characteristics were highly correlated with the BMWP/Col and ABI indices. Therefore, these indices can be used to estimate river water quality and provide information on its functioning.